Risks and Benefits of Central Neck Dissection (CND) in Differentiated Thyroid Carcinoma (DTC) - H.S. Wahyu Purnomo; Erwin D Yulian; Grace Wangge (Jurnal llmu Bedah Indonesia, 2018)
Introduction: The role of central neck dissection (CND) remains controversial in differentiated thyroid cancer (DTC). Risk and benefit of CND is necessary to be identified for judging whether CND will be performed or not. Methods: A literature search was performed in MEDLINE (pubmed) using main keywords such as differentiated thyroid carcinoma (DTC), central neck dissection (CND), total thyroidectomy. The literature had inclusion criteria english language literature with risk and benefit of CND. We used qualitative approach to summary descriptive papers result. Results: Sixteen trials were analyzed. There was no increased risk of recurrent laryngeal nerve (RLN) injury (temporary or permanent), permanent hypocalcemia, or locoregional recurrence when CND was performed in addition to TT. Postoperative temporary hypocalcemia was more common after TT with CND than after TT alone. Conclusion: TT alone results in less surgical morbidity in the immediate postoperative period and an identical locoregional recurrence rate compared with TT plus CND.